2012
DOI: 10.1590/s1516-31802012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition during bone marrow transplantation in patients with pediatric cancer: a prospective cohort study

Abstract: CONTEXT AND OBJECTIVE: Cancer patients undergoing bone marrow transplantation (BMT) often require nutritional therapy due to treatment toxicities. The aim here was to evaluate the use of tube feeding and its applicability, indications, contraindications and complications in these patients. DESIGN AND SETTING: Prospective observational study conducted at a public university in São Paulo between January 2002 and August 2007. METHODS: The patients were followed up daily in the BMT unit by a research dietitian. Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
10
0
4
Order By: Relevance
“…The choice of nutritional therapy for chemotherapy patients follows the principle of "use the intestine when it is functional and can be used safely", and enteral nutrition is preferred (Lee et al, 2017;Garofolo, 2012;Nogueira et al, 2020). Enteral nutrition is not only safe and inexpensive, but also meets the body's normal physiological needs and protects the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of nutritional therapy for chemotherapy patients follows the principle of "use the intestine when it is functional and can be used safely", and enteral nutrition is preferred (Lee et al, 2017;Garofolo, 2012;Nogueira et al, 2020). Enteral nutrition is not only safe and inexpensive, but also meets the body's normal physiological needs and protects the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Garófolo (2012), the main indications for ETF in patients who underwent autologous transplantation were: inadequate oral intake of food and supplements; insufficient intake of food and supplements with malnutrition or weight loss; and severe malnutrition 10 . The same study also reported that 36% of patients who underwent autologous HSCT had some degree of malnutrition at admission 10 . In the present study, the percentage of patients who were underweight or at risk for underweight at admission was 16.7%, and increased significantly to 33.3% at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the percentage of patients who were underweight or at risk for underweight at admission was 16.7%, and increased significantly to 33.3% at discharge. Though there has been an increase in the prevalence of overweight among healthy children in the general population 11 , those who are hospitalized for transplant are usually in the normal weight range 10,12,13 . This was observed in our study, where most patients were of normal weight in the pre-transplant period (59.1%), although this assessment did not consider body composition.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is needed for developing treatment guidelines, including establishing a timeline for initiation of feeding, and determining which patients are most likely to benefit from enteral feeding Hence, for a more precise interpretation of the results, a multicenter study is warranted in order to follow up a larger number of patients, with a periodic complete nutritional assessment and with enteral protocols included as part of the anticancer protocols. [56][57][58][59][60][61]…”
Section: Discussionmentioning
confidence: 99%